Corrosion Properties and Mechanism of Steels - Křivý, Vít (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to promote and disseminate applied research in the field of corrosion of steel structures and technological equipment. Within the text, the focus is firmly placed on the detailed study of corrosion processes affected by specific environments, as well as on the effects of corrosion damage on the reliability and service life of structural components and technological equipment. Special attention is paid to the study of the impact of corrosion processes on pipelines.